2013
DOI: 10.1016/j.foodcont.2013.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Hand hygiene knowledge, attitudes and practices among food handlers at primary schools in Hulu Langat district, Selangor (Malaysia)

Abstract: The purpose of this study was to investigate the hand hygiene knowledge, attitudes and practices of food handlers from 38 primary schools in Hulu Langat district, Selangor State in Malaysia. Hand hygiene knowledge, principally regarding ready-to-eat foods, the existence of bacteria and correct hand-washing methods were lacking among the food handlers. From the observations reported herein, the use of masks and hand-washing with proper technique were neglected by most food handlers. In the demographic profile a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
69
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 21 publications
18
69
1
2
Order By: Relevance
“…Although the KAP of food-handlers had improved somewhat in comparison to a study conducted six years before (Nguyen et al, 2010), they were still relatively poor. The KAP scores of food-handlers in our study were low compared with similar studies conducted in Malaysia (Abdul-Mutalib et al, 2012;Nee & Sani, 2011;Tan, Bakar, Abdul Karim, Lee, &Mahyudin, 2013), andin Brazil, Jordan andCanada (McIntyre, Vallaster, Wilcott, Henderson, &Kosatsky, 2013;Sharif, Obaidat, & Al-Dalalah, 2013;Soares, Almeida, Cerqueira, Carvalho, & Nunes, 2012).…”
Section: Discussioncontrasting
confidence: 82%
“…Although the KAP of food-handlers had improved somewhat in comparison to a study conducted six years before (Nguyen et al, 2010), they were still relatively poor. The KAP scores of food-handlers in our study were low compared with similar studies conducted in Malaysia (Abdul-Mutalib et al, 2012;Nee & Sani, 2011;Tan, Bakar, Abdul Karim, Lee, &Mahyudin, 2013), andin Brazil, Jordan andCanada (McIntyre, Vallaster, Wilcott, Henderson, &Kosatsky, 2013;Sharif, Obaidat, & Al-Dalalah, 2013;Soares, Almeida, Cerqueira, Carvalho, & Nunes, 2012).…”
Section: Discussioncontrasting
confidence: 82%
“…For hand washing and drying, 97.7% of PIC reported that hands should be washed thoroughly after visiting toilet or when exposed to contaminated surface and they know the appropriate way of drying them. This revelation is similar to what Giritlioglu, Batman andTetik, (2011) andTan, Bakar, Abdul Karim, Lee, andMahyudin (2013) have reported (98.8% and 95.3%) respectively for a similar question.…”
Section: Effect Of Pic Intervention On Food Safety Knowledge Within Gsupporting
confidence: 91%
“…In a study of hand hygiene knowledge, attitudes and practices among food handlers in Malaysia. Tan et al (2013) found that in the self-reported hand hygiene practices 89.4% of the food handlers reported that they always use proper hand-washing procedures. However, in realty none of them was doing it correctly.…”
Section: Overall Effect Of Pic Intervention On Food Safety Practicementioning
confidence: 97%
See 1 more Smart Citation
“…However, although hand washing is critical for the production of safe meals, a study of 38 elementary schools in Hulu Langat (Malaysia) found that only 15.3% of the food handlers knew all the steps for proper hand washing and that this activity was neglected by most food handlers 26 .…”
Section: Discussionmentioning
confidence: 99%